A study of risk in construction project in east coast of Malaysia: scaffolding safety - Muhamad Amirull Syahiran, Samsukhidir (2018)
Malaysia industry nowadays are in a good pace due to the improvement based on development and infrastructure. Although through the rapid development, accidents at the work place are always be the main issue especially at the construction site. There are not only common accidents that always happen that need to be concern but also the use of scaffolding at the construction project also one of the deadliest accidents that have happen. Accidents that involve with scaffolding occur due to lack of expertise in handling scaffolding. In addition, accidents involve scaffolding may arise if it is not monitored or properly regulated by the competent person while installing or dismantling scaffolding. Scaffolding accident also can happen depend with the condition of the work place. Besides that, the accidents take place at first are from irresponsible workers that did not take the issue seriously about the use of personal protection equipment while working especially dealing with height. Due to the accidents and lack of knowledge while dealing with scaffold, it can create enormous problems to the environment at the work place and also contractors. A study has been conduct based on the problem to identify the cause of accident. This study will cover the East Coast area of Malaysia. Objective for the study are to identify the types of scaffolding used at construction project. The study also to identify risk of scaffolding that faced by the workers. After the risk towards scaffolding has been identify, then the data analysis will be conducted on preventing the accident occur involve scaffolding. Methodology that will be produce are by distributing questionnaire based on the objective. The data that have been collected from the questionnaire will be analysed by using Microsoft Excel and Relative Important Index which also will be include with bar graph and pie chart. Based on the questionnaire, most of the respondents agreed with the research that has been conduct and suitable method need to be taken by the responsible parties to ensure that use of scaffolding at construction project are secure and ensure that accident involve with scaffolding has not given any negative impact on the project that to be carried out in the future.